2017
DOI: 10.1007/s12011-017-1218-5
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Testicular Toxicity in Male Wistar Rats: Protective Roles of Zinc and Magnesium

Abstract: Cadmium (Cd) is a highly toxic element, which may cause toxicity to most organs in the body. Zinc (Zn) and magnesium (Mg) are essential minerals with probable benefits on Cd harmful effects. Finding an efficient and non-pathological treatment against Cd toxicity seems promising. Fifty adult rats were divided into ten experimental groups of five rats each. The Cd group was treated with 1 mg Cd/kg and the control group received 0.5 cm normal saline. The other eight groups received Zn (0.5 and 1.5 mg/kg) and Mg (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…The sperm morphology was assessed using eosin stain as per the method described by Babaknejad et al (2018). The sperm samples All the values are expressed as mean ± SEM (n 4).…”
Section: Sperm Morphologymentioning
confidence: 99%
“…The sperm morphology was assessed using eosin stain as per the method described by Babaknejad et al (2018). The sperm samples All the values are expressed as mean ± SEM (n 4).…”
Section: Sperm Morphologymentioning
confidence: 99%
“…Consequently, the therapeutic use of magnesium and zinc significantly reduces the effects associated with exposure to cadmium and which confirms their potential protective properties against the pathological toxicity of cadmium [11].…”
Section: Discussionmentioning
confidence: 63%
“…In addressing these effects, significant evidence is accumulating to suggest that essential elements (such as magnesium and zinc) can counteract the effects of cadmium by exhibiting protective properties at the cellular level, thus helping to prevent or reduce its adverse effects on health. Conversely, their deficiency can also increase the accumulation of cadmium within internal organs, thereby increasing its toxic effects [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown the protective function of zinc (60 mg/L) in preventing Cd-induced testicular toxicity in male rats via restoration of disheveled-associated activator of morphogenesis 1 (DAAM1) expression after gestational and lactational exposure to Cd (Chemek et al, 2017). Co-administration of zinc and magnesium (0.5 and 1.5 mg/kg) to rats significantly improved the sperm quality and caused a reduction in testicular MDA content (Babaknejad et al, 2018). Com-…”
Section: Trace Metalsmentioning
confidence: 99%
“…A recent study has shown the protective function of zinc (60 mg/L) in preventing Cd‐induced testicular toxicity in male rats via restoration of disheveled‐associated activator of morphogenesis 1 (DAAM1) expression after gestational and lactational exposure to Cd (Chemek et al, 2017). Co‐administration of zinc and magnesium (0.5 and 1.5 mg/kg) to rats significantly improved the sperm quality and caused a reduction in testicular MDA content (Babaknejad et al, 2018). Combined treatment with selenium (0.1 parts per million [ppm]) and zinc (500 ppm) provided more significant protection against testicular injury in Cd‐exposed rat, as evidenced by the entire restoration of testicular antioxidant status and sperm quality (Said, Banni, Kerkeni, Said, & Messaoudi, 2010).…”
Section: Remedies For the Management Of Cadmium‐induced Testicular Tomentioning
confidence: 99%